2018
DOI: 10.1155/2018/4217259
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Insulin-Like Growth Factor 2 mRNA-Binding Protein 2 in Cancer and Cancer Stem Cells

Abstract: RNA-binding proteins (RBPs) mediate the localization, stability, and translation of the target transcripts and fine-tune the physiological functions of the proteins encoded. The insulin-like growth factor (IGF) 2 mRNA-binding protein (IGF2BP, IMP) family comprises three RBPs, IGF2BP1, IGF2BP2, and IGF2BP3, capable of associating with IGF2 and other transcripts and mediating their processing. IGF2BP2 represents the least understood member of this family of RBPs; however, it has been reported to participate in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
128
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 146 publications
(250 reference statements)
6
128
0
Order By: Relevance
“…Table 5) and could be involved in circRNA nuclear export or otherwise in circRNA localization. For instance, the IGF2BPs, which we found on average have more target sites in circularizing exons, are regulators of essential mRNAs in tumorigenesis and are important players of mRNA stability and transportation to subcellular compartments (59) . Accordingly, IGF2BP3 was found to bind to several circRNAs (29) .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Table 5) and could be involved in circRNA nuclear export or otherwise in circRNA localization. For instance, the IGF2BPs, which we found on average have more target sites in circularizing exons, are regulators of essential mRNAs in tumorigenesis and are important players of mRNA stability and transportation to subcellular compartments (59) . Accordingly, IGF2BP3 was found to bind to several circRNAs (29) .…”
Section: Discussionmentioning
confidence: 80%
“…CircCDYL has been suggested to suppress cell growth by inhibiting MYC protein expression levels in bladder cancer through an unknown mechanism (58) . IGF2BP1 and IGF2BP2 possess oncogenic roles and positively regulate the expression of various oncogenes (reviewed in (50,59) ). We evaluated how circCDYL and RBP depletion affect 50 hallmarks of cancer (60) .…”
mentioning
confidence: 99%
“…[3,9a,b] Recent studies have documented many maternal proteins in mice, including YAP1, MED13, and TLE6, as having essential functions during ZGA. [15,16] IMP2 regulates RNA trafficking, the processing of transcripts that encode key subunits in mitochondrial respiratory chain complexes, and IGF2 mRNA translation. [12,13] IMP2 has two RNA-recognizing motifs and four KH domains that control its binding specificity for RNA.…”
Section: Introductionmentioning
confidence: 99%
“…8 Recently, some case-control studies have focused on the relationship of IGFBP3 and IGF1 single nucleotide polymorphisms (SNPs) with the risk of cancer. 19,20 Dai et al 21 reported that IGF2BP2 is a tumor promoter, which drives tumor proliferation through HMGA1 and mRNAs IGF2. 12 Also, significant association with the survival of breast cancer in Chinese premenopausal women was identified for IGFBP3 rs3110697 G > A.…”
Section: Introductionmentioning
confidence: 99%